2015
DOI: 10.1371/journal.pone.0142404
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control of Biomedicinal Allergen Products – Highly Complex Isoallergen Composition Challenges Standard MS Database Search and Requires Manual Data Analyses

Abstract: Allergy against birch pollen is among the most common causes of spring pollinosis in Europe and is diagnosed and treated using extracts from natural sources. Quality control is crucial for safe and effective diagnosis and treatment. However, current methods are very difficult to standardize and do not address individual allergen or isoallergen composition. MS provides information regarding selected proteins or the entire proteome and could overcome the aforementioned limitations. We studied the proteome of bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 35 publications
(46 reference statements)
1
52
0
1
Order By: Relevance
“…New York, NC. The identity of the protein was confirmed by in‐gel digestion followed by LC/MS analysis according to with slight modifications as specified in …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…New York, NC. The identity of the protein was confirmed by in‐gel digestion followed by LC/MS analysis according to with slight modifications as specified in …”
Section: Methodsmentioning
confidence: 99%
“…NewYork, NC. The identity of the protein was confirmed by in-gel digestion followed by LC/MS analysis according to25 with slight modifications as specified in 26. 2.4 | IgE-binding and cross-reactivity assaysSpecific IgE values were determined by using experimental Immuno-CAP 27 for rTri tu 14 and commercially available ImmunoCAPs for rTri a 14.01 (f433), rPru p 3 (f420), and T. aestivum wheat (f4) (Thermo Fisher Scientific).…”
mentioning
confidence: 99%
“…In addition, they reported on a set of reference mAb that were fivefold less sensitive to the reference allergen Bet v 1.0101 than to Bet v 1 in natural extracts. At the Paul‐Ehrlich Institute, we demonstrated that natural birch pollen extract includes a mixture of isoforms, at least 18 different sequence variants of Bet v 1, including an isoallergen that had not been previously been detected at the protein level . Having identified these issues, the ELISA assays for Bet v 1 were fully characterized in 2012 and validated in 2016 .…”
Section: Standardization Of Allergenic Extractsmentioning
confidence: 99%
“…For purified natural and recombinant proteins the level of purity needs to be determined and additional protein contaminations with and without allergenic activity identified. Also the range of potential isoforms with varying IgE binding capacity needs to be defined as a reference set of proteins . Especially for recombinant proteins lipopolysaccharide (LPS) contamination should be ruled out since this could affect further immunization/sensitization studies.…”
Section: Introductionmentioning
confidence: 99%